Familie und Gesellschaft in Birgit Weyhes Graphic Novel Im Himmel ist Jahrmarkt - Lovrić, Goran (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
Birgit Weyhe’s Im Himmel ist Jahrmarkt (2013) is thematically one of the autobiographically based graphic novels that deal with family history in the context of the political and social events of the 20th century and is thus related to the generational novel. In the book, Weyhe researches and tells the story of her ancestors, attempting to gather information about the grandparents’ generation and thus preserve the family memory. She only partially succeeds in this with the help of memories, letters, and photographs, which is why she fills gaps in knowledge with anecdotes and fictional interludes. She does not limit herself to the Nazi era, however, but also deals with other private and general human and social themes of the post-war period, such as betrayal, fraud, clandestine abortion, repressed homosexuality, etc. Because these topics are still relevant today and the graphic novel format appeals particularly to a young audience, the book is particularly suitable for use in middle schools and universities, which will be illustrated in this paper with examples.